TECHNOLOGY IN LANGUAGE LEARNING IN EARLY CHILDHOOD CURRICULUM - GOPAL, PRANITA (THE PRIMARY TEACHER, 2012)
The desire to communicate is one of the basic needs of human beings and we feel this need as soon as we step into this world. Language is the agent that helps us fulfil this need of ours and as we grow our language acquisition process is strengthened. One of the pillars of a good early childhood curriculum is the manner in which language development experiences are planned for a child– as the child learns the rules of the language without any formal instructions. Technology has now found its place in the early education environment along with books, flannel boards, finger paints, markers, play dough, and other media. As a result, the use of technology in an early childhood setting requires that each of us, as early childhood educators, continue to learn as much as we can about technology issues and trends. Computers and Tablet PCs, along with developmentally appropriate software, interactive CDs, DVDs, and cassette tape audio recorders, can make a unique contribution to the education of young children. How appropriately technology is used is more important than just using it. This paper presents examples of using technology appropriately in the language learning classroom by documenting various studies existing in the area. It also discusses how assistive technology can assist children with special needs as they strive to participate in a regular educational environment. The paper also provides a checklist for early childhood educators and curriculum developers to decide on incorporating technological interventions so that learning experiences are augmented and also other child-related developmental activities do not take a back-seat.